Role of glucose‐dependent insulinotropic polypeptide in adipose tissue inflammation of dipeptidylpeptidase 4‐deficient rats. (29th May 2013) - Ben‐Shlomo, Shani; Zvibel, Isabel; Varol, Chen; Spektor, Lior; Shlomai, Amir; Santo, Erwin M.; Halpern, Zamir; Oren, Ran; Fishman, Sigal
Abstract : Objectives: Dipeptidyl peptidase 4 (DPP4) inhibitors, used in obese diabetic patients, reduce inflammation in several models. The role of chronic DPP4‐deficiency (DPP4‐) in diet‐induced obesity with respect to insulin sensitivity and adipose tissue inflammation was investigated. Design and Methods: Insulin resistance was induced by 2 months high fat diet (HFD). In vitro effects of glucose‐dependent insulinotropic polypeptide (GIP) were assessed in adipose tissue explants and stromal vascular fraction (SVF). Results: HFD‐fed DPP4‐rats gained significantly more weight and visceral fat mass, yet were more insulin sensitive. Adipose tissue of DPP4‐ rats demonstrated increased adipocyte maturation and increased expression of enzymes involved in triglyceride uptake and synthesis, yet increased adiponectin mRNA, reduced mRNA of proinflammatory cytokines and reduced vascular adhesion molecules, suggesting reduced inflammation. In vitro and in vivo experiments explored the role of GIP in inducing this phenotype. Indeed, we demonstrated that GIP directly enhanced adiponectin expression in rat and human adipose tissue explants and in SVF. Lastly, GIP administration to normal or HFD‐fed rats elevated serum adiponectin and improved their glucose tolerance test. Conclusion: In a HFD model, DPP4‐rats exhibited reduced adipose tissue inflammation and improved insulin resistance, which may be mediated in part by GIP induction of adiponectin.